MEMBACA BAHASA RUPA SASTRA VISUAL GAMBAR DINDING KOMUNITAS SUKU DAYAK HINDU BUDHA BUMI SEGANDU INDRAMAYU - Asep Deni Iskandar (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
Representation of teaching in the form of literary visualization of panel wall picture alongside fortress of Padepokan at Suku Dayak Bumi Segandu Indramayu community. The visual form at overall panel wall pictures still be shown the existence of touch by way of drawing typically used by the past ancestors with the system space-time-plane (STP). The use of system STP at wall picture become the evidence that the tradition pattern still exist in the middle of domination of the visual language of the West with the system naturalistic-perspective-moment opname (NPM) that assumed universal and modern. Keyword : The wall picture, literary visualization, space-time-plane, naturalistic-perspectivemoment opname